Thematic Directed Reading Lessons and Listening Comprehension among Filipino Struggling Readers in a Community-based Program - Sandicho, John Paolo V; Padilla, Portia P (Alipato, A Journal of Basic Education; Vol 13 (2022), 2023)
Thematic directed reading lessons promote connected learning and student engagement. In the local context, there remains a gap in the literature on how this type of lessons can be used in improving listening comprehension skills. Thus, this exploratory multiple-case study seeks to describe the use of thematic directed reading lessons in improving struggling readers’ listening comprehension skills. Four elementary students, who read below grade-level expectations, participated in the five sessions conducted in a community-based literacy center. Researcher-constructed and expert-validated thematic directed reading lesson plans and listening comprehension tests in Filipino were used. The results of the tests were examined per case. As predicted, listening comprehension skills improved after the lessons. In summary, the scores of all participants in the post-test and delayed post-test were higher than their pretest scores. Post-test gains in noting details were seen in the scores of all participants, whereas an increase in scores in sequencing events, inferring character feelings, and connecting story details to one’s life was not consistently observed. This suggests that thematic directed reading lessons can be a viable option in helping children improve in listening comprehension, although this is consistently shown only in the skill of noting details.